β-galactosidase immobilization on controlled pore silica - Trevisan, H. C. [UNESP]; Bergamo, E. P. [UNESP]; Contiero, Jonas [UNESP]; Hojo, Ossamu [UNESP]; Mont, R. [UNESP] (FapUNIFESP (SciELO), 1997)
The immobilization of β-galactosidase from Kluyveromyces fragilis on controlled pore silica was investigated. Immobilization was performed on amino silica activated with glutaraldehyde and the product was applied to the hydrolysis of lactose of whey. The behaviors of the soluble and immobilized enzyme were compared by using whey and a lactose solution as the substrate. With the aim of optimizing the method, parameters such as the amount of glutaraldehyde and the size of the particles were evaluated by comparing activities and stabilities on batch and continuously fluidized bed reactors.
Keywords: Aldehydes; Fluidized beds; Hydrolysis; Porous materials; Silica; Sugars; Lactose; Porous silica; Enzyme immobilization